Three-Dimensional Digital Breast Tomosynthesis versus Two-Dimensional Mammography in Detection and Characterization of Breast Lesions Keeping Biopsy as the Gold Standard - Akbar, Hina; Ibrahim, Nadeem; Tahir, Sadia; Arfat, Yasir; Irshad, Mishaal; Muhammad Junaid (Indus Journal of Bioscience Research, 2025)
Background: Breast cancer is a major cause of cancer death in women throughout the world. Accurate detection at an early stage is extremely important to improve outcomes. Digital breast tomosynthesis (DBT) has potential advantages over conventional digital mammography (DM) due to reduction of tissue superimposition. This study is being conducted with the aim to compare the diagnostic performance of the three-dimensional digital breast tomosynthesis and two-dimensional digital mammography in the detection and characterization of the breast lesions, using histopathology as the gold standard. Methods: This cross-sectional validation study was conducted in the radiology department of a Combined Military Hospital, Gujranwala from 31 January 2025 to 31 May 2025. Female patients aged 25-70 years who underwent both the digital mammography and digital breast tomosynthesis and had a breast lesions categorized as BI-RADS categories three to five were included. All participants afterwards underwent histopathological evaluation through the biopsy or surgical excision. Imaging findings were interpreted independently by the experienced radiologists who were blinded to the histopathological results. Sensitivity, specificity, positive predictive value, negative predictive value, and overall diagnostic accuracy were measured for both imaging modalities. Results: The mean age of participants was found to be 48.32+12.96 years. DBT was shown to have improved diagnostic performance over DM, having higher sensitivity (92.3% vs. 84.6%), specificity (79.4% vs. 76.5%), PPV (77.4% vs. 73.3%), NPV (93.1% vs. 86.7%) and overall accuracy (85.0% vs. 80.0%). Conclusion: 3-D digital breast tomosynthesis is a superior modality to conventional mammography for the detection and characterization of breast lesions in terms of sensitivity, specificity, and negative predictive value. Its superior performance in diverse patient subgroups supports the role of this modality as a preferred modality of imaging, especially in symptomatic patients and patients of challenging breast compositions.